Comparative Study of Bacillus amyloliquefaciens X030 on the Intestinal Flora and Antibacterial Activity Against Aeromonas of Grass Carp - Zhou, Pengji; Chen, Wenhui; Zhu, Zirong; Zhou, Kexuan; Luo, Sisi; Hu, Shengbiao; Xia, Liqiu; Ding, Xuezhi (Frontiers in Cellular and Infection Microbiology, 2022)
Beneficial microorganisms to control bacterial diseases has been widely used in aquaculture, Bacillus amyloliquefaciens (BaX030) as a probiotic feed additive was a commonly biological control method. Added sucrose promoted the growth of BaX030, and the yield of its antibacterial substance macrolactin A was enhanced by 1.46-fold. A total of 2055 proteins were screened through proteomics, with 143 upregulated and 307 downregulated. Differential protein expression analysis and qRT-PCR verification showed that the pentose phosphate pathway and the fatty acid synthesis pathway were upregulated, thereby providing sufficient energy and precursors for the synthesis of macrolactin A. The influence of some potential regulatory factors (SecG, LiaI, MecG and ComG) on macrolactin A was discovered. After grass carp were fed with BaX030, the abundance of probiotics (Fusobacterium, Proteobacteria, Gemmobacter) were higher than the control group, and the abundance of potential pathogenic bacteria (Planctomycetes, Aeromonas) were significantly lower than the control group. The cell and challenge experiments showed that BaX030 can significantly increase the expression of C3 and IL8 in the liver and kidney, which decreases the risk of immune organ disease. Moreover, BaX030 effectively reduced the mortality of grass carp. The results revealed that BaX030 can significantly improve the structure of the intestinal flora, enhance immunity and it is beneficial to the control of grass carp Aeromonas.